35. Laser in neurosurgery: Critical issues in security management. (December 2018) - Ferrari, M.B.; Mainardi, H.S.; Artuso, E.; Calderoni, F.; Rottoli, F.; Torresin, A.
Abstract : Purpose: Safe use of LASER in Neurosurgery. Methods: The Neurosurgery Department of Niguarda Hospital has recently acquired a class 4 LASER, with a wavelength of 2010 nm, for the resection of brain tumors. This high-technological device represents a great innovation for neurosurgeons with remarkable improvements in the operating mechanisms but it requires, at the same time, a particular attention in the choice of the other tools, such as endoscopes and microscopes. The protection of the operator's eyes during surgery is particularly critical. Protection glasses, provided to the whole staff, interfere with the usual procedure of the neurosurgeon who keeps his eye in contact with the eyepiece. A possible option could be the introduction of a protective lens within the microscope optics, as in ophthalmology LASERs. We tried to solve the problem on our own. Results: The introduction of this LASER brought to the prohibition of use with some particular tools and to the need of modify other devices. The microscope in Niguarda's Neurosurgery Department is the mod. M530 produced by Leica. The LASER attenuation required to the lens for a safe use has been calculated, taking into account the need to visualize the pointing laser and the markers, necessary for the identification of the tumor mass. Since the microscope optics does not guarantee this protection, a system has been designed to hold an additional lens with the required protection on the microscope. Conclusions: In order to provide a safe use of the new LASER, the staff has been equipped with specific protective glasses and the use of the disposable endoscope has been forbidden. The designed system is put into production and the use will be evaluated by the neurosurgeons.